Cathepsin B in urological tumors: unraveling its role and therapeutic potential - Zhaojie Yan; Guansong Zheng; Junrong Zou; Xiaofeng Zou; Keqiang Chai; Guoxi Zhang (Discover Oncology)
Abstract Cathepsin B(CTSB) is a key protease within the lysosomal protease family and is recognized as a tumor-promoting factor that exerts a substantial impact on cancer progression. It plays a critical role in the initiation, proliferation, metastasis, and angiogenesis of cancer, significantly advancing the disease. This review offers a concise overview of the structure and biological functions of CTSB, clarifying its relationship with cancer and the role it plays in the disease's progression. Additionally, we discuss the association between CTSB and several common malignant tumors of the urinary system, highlighting its potential role and clinical significance within these tumors, as well as the challenges that remain.